PREVALENCE OF GENETIC MARKERS OF RESISTANCE TO ANTIBIOTICS IN BIOFILM-FORMING STRAINS OF OBLIGATE AND ELECTIVE ANAEROBES - V. N. Tsarev; E. V. Ippolitov; E. N. Nikolaeva (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Comparative study of frequency of detection of genetic markers of resistance to antibiotics forming in anaerobic bacteria under the conditions of mixed biofilms in a clinical setting and comparison of data of phenotypic and genotypic methods of study. Materials and methods. 66 strains of bacteria forming biofilm with PCR detection of antibiotics were studied: Streptococcus sanguinis, Streptococcus salivarius, Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Klebsiella pneumoniae, Pseudomonas aeruginosa and anaerobic pathogens - Porphyromonas gingivalis, Tannerella forsythia, Parvinonas micra, Prevotella intermedia. Modelling of microbial biofilms in vitro and scanning electron microscopy were carried out. Results. The studied strains of resident and pathogenic microbiota were established to have genes that code resistance to P-lactam antibiotics, carbapenems, macrolides, tetracyclines. Genetic markers of resistance to p-lactam antibiotics (STX-M и МЕСА - cepha-losporines), including carbapenems (VIM and NDM, but not Oxa-48), glycopeptides (VanA and VanB), macrolides (ERM), tetracycline (Tet) and QNRB plasmids (fluoroquinolones) were detected in strains by PCR. Conclusion. The most frequently used preparations in dental practice - metronidazole and lincomycin (for the last 20 - 30 years) have shown the highest number of resistant strains - 52.3 and 22.7%, respectively. The frequency of detection of genetic markers of resistance to other studied preparations did not exceed 2.5 - 11.4%. Minimal quantity of resistant strains of anaerobic bacteria was detected for carbapenems and fluoroquinolones.